BUSINESS MODEL CANVAS (BMC) SEBAGAI KERANGKA INOVASI DALAM PENDIDIKAN MATEMATIKA: SYSTEMATIC LITERATURE REVIEW - Rusdy Habsyi; Rusli Rusli (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study systematically examines the application of the Business Model Canvas (BMC) as an innovation framework in mathematics education during the period of 2020–2025. Employing a Systematic Literature Review (SLR) guided by the PRISMA, the study reviewed 298 articles retrieved from Scopus, ScienceDirect, SpringerLink, and Sinta databases. Following a rigorous inclusion–exclusion screening process, 13 relevant studies were identified and analyzed thematically. The findings reveal that the implementation of BMC has transformed the direction of mathematics education research from merely theoretical development toward practical and sustainable innovation. The nine-block structure of BMC assists researchers in designing value propositions, identifying user segments, and developing sustainability strategies in the creation of research-based media, learning modules, and educational technology (edutech) products. Moreover, integrating BMC fosters scientific entrepreneurship among lecturers and students, bridging academic research with the demands of the digital education market. Theoretically, this review broadens the role of mathematics education as a transdisciplinary field that integrates pedagogical, technological, and economic dimensions. Practically, BMC can be incorporated into university curricula—particularly in courses on Learning Innovation and Educational Entrepreneurship—to cultivate creativity and strategic thinking among pre-service teachers. The study recommends that each development-oriented research project in mathematics education include a BMC-based business model to ensure sustainability and to encourage cross-disciplinary collaboration among education, technology, and economics. Consequently, BMC functions not only as a business planning tool but also as a strategic approach to transforming educational research into creative, relevant, and impactful mathematics education practices.